Sappers and Miners: The Flood beneath the Sea - Fenn, George Manville, 1831-1909; Hurst, Hal, 1865-1938 (Salt Lake City, UT : Project Gutenberg, 2007)
"Sappers and Miners: The Flood beneath the Sea" by George Manville Fenn is a novel written in the late 19th century. The story unfolds in Cornwall, primarily around an ancient tin mine, and revolves around the characters Colonel Pendarve, his son Gwyn, and their friend Joe Jollivet, as they navigate themes of adventure, risk, and the enduring allure of hidden wealth. The opening sets a light yet suspenseful tone, hinting at an exploration of both the physical and metaphorical depths of the mine, as well as the boys' daring curiosity. At the start of the novel, readers are introduced to the Pendarve family enjoying a breakfast filled with lively conversation about fishing and local gossip, which touches on the past riches of the old Ydoll mine. Gwyn, a spirited young boy, is eager to explore the ancient mine despite his father's cautions, and his friendship with Joe Jollivet adds camaraderie to their adventurous spirit. The plot quickly escalates as the boys, intrigued by a local captain$1 (Bs claims of treasure, begin their exploration, leading to a harrowing incident when Gwyn descends into the mine only to encounter a life-threatening situation. This thrilling opening sets the stage for a tale woven with suspense and discovery, appealing to readers who enjoy adventure and the unconventional paths children may take in search of excitement. (This is an automatically generated summary.)s
Release date is 2007-05-08
Produced by Nick Hodson of London, England
Keywords: Dogs -- Juvenile fiction; Conduct of life -- Juvenile fiction; Friendship -- Juvenile fiction; Fathers and sons -- Juvenile fiction; Courage -- Juvenile fiction; Parent and child -- Juvenile fiction; Cornwall (England : County) -- Juvenile fiction; Tin mines and mining -- England -- Juvenile fiction